IRAN: ILLOGICAL ELECTION OR THE END OF THE REFORM ERA - MESAMED, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2005)
Iran has no equal in the Muslim world in terms of population size and demographic situation (71 million people), oil supplies (second largest in the world), and special features of its people, military power, and nuclear strivings. And as far as the political destiny of Islam, international terrorism, and the future of the Middle East, shuddering in a convulsive fit, is concerned, this country is again inciting Islamic theocracy against the democratic model of the West.1 Of course, this brief and largely subjective description of Iranian reality (as of June 2005) highlights only the most general features of the current situation in a country held in the grips of a systemic state-political crisis: socioeconomic and political life is still extremely tense. This situation can be explained by the policy failure of both the moderate and the radical reformers who grouped around President Hojatoleslam Seyyed Mohammad Khatami in 1997-2005 but were un-able to bring about any successful transformation of society. Even though political life did undergo a certain amount of democratization at the beginning of this president’s rule (liberal newspapers appeared, but were soon closed, and the number of political parties, associations, and movements increased to two hundred, in particular, the secular party Karagozian and the rightist-centrist Mosha Karat-e Islami were formed),the economic policy of the reformers did not achieve any palpable results with respect to ensuring social justice and social guarantees for the poor strata of the population, eliminating unemployment, and creating new jobs. The extremely modest rise in budget employee salaries, pensions, and stipends, as well as in subsidies for the poor, traditional for Islamic Iran, hardly made a dent in a situation beset by galloping inflation and essentially universal corruption. The positive changes in investments, including foreign, also made little impact. So, it is sad but true that the reformers in Iran’s domestic political milieu were unable to throw anything new in the face of the conservatives who rallied round the country’s religious leader, Ayatollah Ali Khamenei. And this is not surprising: President Khatami himself has often openly admitted that he only implements, but in no way makes important decisions. The country depends entirely on Ayatollah Khamenei, who holds all the reins to governance.